PATH52 Parkinsonism incidence in north-east Scotland: the PINE study. Issue 11 (22nd October 2010) - Counsell, C; Gordon, J; Primrose, W; Harris, C; Caslake, R
Abstract : Background: There have been few high-quality incidence studies of parkinsonism/Parkinson's disease (PD) worldwide and none from Scotland. Methods: We performed a population-based prospective incidence study of degenerative or vascular parkinsonian disorders from 37 general practices (population 317 884) in and around Aberdeen over 3 years. Patients were identified by direct referral by GPs or hospital physicians/psychiatrists, by searching referral letters, and by searching GP databases and hospital discharge data. Incident patients had to have two or more of the cardinal motor symptoms. The most likely clinical diagnosis was made after assessment by a movement disorder expert. Incidence rates were calculated for all parkinsonism combined and for PD specifically and were also compared by age, sex and socioeconomic status. Results: By August 2009, 250 incident patients with parkinsonism had been identified (mean age 74 years, 152 men), 151 (88 men) with a baseline clinical diagnosis of PD. The crude annual incidence of parkinsonism was 26 per 100 000 (95% CI 23 to 29.5) and PD 16 per 100 000 (95% CI 13 to 18). Incidence increased over the age of 60 with a peak between 80 and 89 years (PD 137 per 100 000). PD was more common in men (1.9:1) but there was no difference by socioeconomic status. Conclusion: The incidence of parkinsonism/PD in north-east Scotland is similar to other high-quality studies but with a significantly higher mean age of diagnosis.